Characterisations of Europe's integrated water vapour and assessments of atmospheric reanalyses using more than 2 decades of ground-based GPS - Yuan, P.; Van Malderen, R.; Yin, X.; Vogelmann, H.; Jiang, W.; Awange, Joseph; Heck, B.; Kutterer, H. (2023)
The ground-based Global Positioning System (GPS) has been used extensively to retrieve integrated water vapour (IWV) and has been adopted as a unique tool for the assessments of atmospheric reanalyses. In this study, we investigated the multi-temporal-scale variabilities and trends of IWV over Europe by using IWV time series from 108 GPS stations for more than 2 decades (1994-2018). We then adopted the GPS IWV as a reference to assess six commonly used atmospheric reanalyses, namely the Climate Forecast System Reanalysis (CFSR); ERA5; ERA-Interim; the Japanese 55-year Reanalysis (JRA-55); the Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2); and NCEP-DOE AMIP-II Reanalysis (NCEP-2). The GPS results show that the peaks of the diurnal harmonics are within 15:00-21:00 in local solar time at 90 % of the stations. The diurnal amplitudes are 0-1.2 kg m-2 (0 %-8 % of the daily mean IWV), and they are found to be related to seasons and locations with different mechanisms, such as solar heating, land-sea breeze, and orographic circulation. However, mismatches in the diurnal cycle of ERA5 IWV between 09:00 and 10:00 UTC as well as between 21:00 and 22:00 UTC were found and evaluated for the first time, and they can be attributed to the edge effect in each ERA5 assimilation cycle. The average ERA5 IWV shifts are -0.08 and 0.19 kg m-2 at the two epochs, and they were found to be more significant in summer and in the Alps and in Eastern and central Europe in some cases. Nevertheless, ERA5 outperforms the other reanalyses in reproducing diurnal IWV anomalies at all the 1-, 3-, and 6-hourly temporal resolutions. ERA5 is also superior to the others in modelling the annual cycle and linear trend of IWV. For instance, the IWV trend differences between ERA5 and GPS are quite small, with a mean value and a standard deviation of 0.01 % per decade and 0.97 % per decade, respectively. However, due to significant discrepancies with respect to GPS, CFSR and NCEP-2 are not recommended for the analysis of IWV trends over southern Europe and the whole of Europe, respectively.